Comparative Analysis of the Mental Health of Nurses in the Covid-19 Patient Care Room and Non-Covid-19 Patient Care Room - Henny Animarita Saragih; Khotimah Khotimah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Coronavirus Disease 2019 (Covid-19) has a very high transmission and death rate. People who are most at risk of contracting Covid-19 are people who are in close contact with Covid-19 patients, including health workers. Many health workers experience stress and mental health problems due to workload, stigma, fear of infection and life-threatening conditions. The purpose of this study was to determine the differences in the mental health of nurses in the room for Covid-19 patients and in the non-Covid-19 patient room. The research design used comparative observational analytics. The population was all nurses in the Covid-19 room and the non-Covid-19 room totaling 249 respondents. The number of research samples was 60 respondents. sampling technique using cluster random sampling. Measurement of mental health using the Self Reporting Questionnaire (SRQ) instrument. Data analysis using Chi Square statistical test (sig < 0.05), and Odds Ratio (OR). The chi square test results sig 0.000. Shows that there is a difference in the mental health of nurses in the Covid-19 patient room with nurses in the non-Covid-19 patient room. The Odds ratio value of 13.000 shows that nurses in the rooms for Covid-19 patients have a tendency to have mental health disorders 13 times greater than nurses in the rooms for non-Covid-19 patients. The spread of Covid-19 is very fast and the death rate continues to increase, causing nurses to experience fear and anxiety which results in mental health disorders. Increased self-resilience is very much needed and further screening is needed to get treatment precisely.